ОСОБЕННОСТИ ФОРМИРОВАНИЯ ВЫХОДНОГО НАПРЯЖЕНИЯ И ВХОДНОГО ТОКА МАТРИЧНЫХ ПРЕОБРАЗОВАТЕЛЕЙ ПРИ УПРАВЛЕНИИ С ИСПОЛЬЗОВАНИЕМ СКОЛЬЗЯЩЕГО РЕЖИМА - Мысак, Т.В. (Інститут електродинаміки НАН України, Київ, 2012)
The object of the paper is the matrix converter with input and output LC-filter controlled in sliding mode. The use of the vector approach and the simplex algorithms under control synthesis in a sliding mode allows to provide high dynamic performance and quality of the output voltage, the reduced number of switches and the input current approximately sinusoidal. The results of research based on the digital model are presented. References 9, table 1, figures 9.